Study of fatigue life on aluminium composites – fly ash received T6 heat treatment and artificial aging - Achmad, Zainun; Ismail, Al Emran; Harimon, Mohd Azhar (Seventh Sense Research Group, 2021)
In the manufacture of aluminium composites, reinforcement in the form of coal base ash, which has been through an electroless process, is needed, which functions to coat the fly ash so that it sticks to the aluminium metal during casting. The strength of the aluminium alloy material does not only depend on the concentration of the alloy metal but also how the process is treated until the aluminium is ready for use. Heat treatment of T6 with a dissolving temperature of 510 ° C for 1 hour and 2 hours and continued with artificial aging at 120 ° C, 140 ° C and 160 ° C was held for 2 hours. Fatigue is a major cause of the malfunction. From the fatigue test, the highest fatigue life with a load of 087 σu can be seen in the specimens that received heat treatment of T6 510 ° C with a dissolving hold time of 1 hour and an aging temperature of 120 ° C for 2 hours, namely 3. 466 cycles and the lowest fatigue life in specimens that received heat treatment of T6 510 ° C with a dissolving hold time of 2 hours and an aging temperature of 160 ° C for 2 hours, namely 440 cycles. The highest fatigue life with load σy is seen in the specimens that received heat treatment of T6 510 ° C with a dissolving time of 1 hour and an aging temperature of 140 ° C for 2 hours, namely 32,566 cycles and the lowest fatigue life in specimens that received heat treatment T6 510 ° C with a dissolving hold time of 2 hours and an aging temperature of 160 ° C for 2 hours, namely 11,333 cycles.